The Relationship between Bullying and Self-Confidence Levels in Adolescents - Feri Agustriyani; Rizki Yeni Wulandari; Apri Rahma Dewi; Chandra Pratama (GLOBAL HEALTH SCIENCE GROUP, 2025)
Adolescence is one of the period to be experienced individual in the his life , where in period This will experience Lots change in himself . As a result changes experienced , can formed inappropriate behavior Good like violence . violence No only happen to yourself Alone but also to other people. One of form violence that often appears in adolescents is behavior bullying .bullying is behavior aggressive that can in the form of physical , psychological , or verbal. Behavior bullying give impact bad to victims of bullying , including having an impact on low self awareness , anxiety , fear even depression , insomnia, difficulty concentrate and not believe themselves .Types of research is study quantitative with analytical survey use approach cross sectional with design survey analytics and approaches cross-sectional , sample taken use method Proportional Stratified Random Sampling from population of 230 respondents , resulting in 146 respondents . Analysis bivariate using statistical tests Gamma . Analysis results show that from 146 respondents low bullying was found at 65.1%, moderate bullying at 33.6%, high bullying at 1.4%, while variable level trust self low 64.4%, level trust self is 34.2%, and the level trust self high 1.4%. From the gamma test results obtained p- value = 0.000 < 0.05 means there is connection bullying with level trust themselves in adolescents . For the parties school and parents provide system support to teenager For increase trust self and for teenagers to avoid conflict with Friend same age and brave say not on behavior bullying.